Pendampingan Pemanfaatan Kulit Jeruk Pamelo Menjadi Sabun dan Biobaterai di MTS NU Raden Umar Said - Malichatin, Hanik; Rahayu Prasetyo, Dody (LPPM Universitas Trunojoyo Madura, 2023)
Bath soap and electricity are people's daily needs. Skills in making bath soap and biobatteries (producing electricity) are expected to reduce public expenses every month. On the other hand, organic waste (pamelo orange peel) is found in Sunan Muria religious tourism area. This has the potential to be used as a basic ingredient for soap and bioelectricity because it is a natural ingredient that is safe to use. The target of this assistance is science teacher and MTs NU student Raden Umar. This is because students have knowledge of these basic materials obtained from learning science but cannot process them into useful products. This successfully made product can later be used by family members of the student. This mentoring activity consists of stages of preparation, implementation, and evaluation. Interviews and documentation are conducted at each stage, then analyzed descriptively. The results obtained through this assistance are: 1) the students have been able to make soap and biobatteries well despite the obstacles in using practicum tools and 2) the madrasah is satisfied with the implementation of this mentoring activity. The follow-up of this activity is the madrasah compiling an extracurricular activity program containing research activities based on local potential in the Kudus area. In addition, Tadris IPA IAIN Kudus became an expert staff in the organizational structure of these extracurricular activities.